Reducing prejudice and promoting positive intergroup attitudes among elementary-school children in the context of the Israeli–Palestinian conflict. (August 2016) - Berger, Rony; Benatov, Joy; Abu-Raiya, Hisham; Tadmor, Carmit T.
Abstract: The current investigation tested the efficacy of the Extended Class Exchange Program (ECEP) in reducing prejudicial attitudes. Three hundred and twenty-two 3rd and 4th grade students from both Israeli–Jewish and Israeli–Palestinian schools in the ethnically mixed city of Jaffa were randomly assigned to either intervention or control classes. Members of the intervention classes engaged in ECEP's activities, whereas members of the control classes engaged in a social–emotional learning program. The program's outcomes were measured a week before, immediately after, and 15 months following termination. Results showed that the ECEP decreased stereotyping and discriminatory tendencies toward the other group and increased positive feelings and readiness for social contact with the other group upon program termination. Additionally, the effects of the ECEP were generalized to an ethnic group (i.e., Ethiopians) with whom the ECEP's participants did not have any contact. Finally, the ECEP retained its significant effect 15 months after the program's termination, despite the serious clashes between Israel and the Palestinians that occurred during that time. This empirical support for the ECEP'S utility in reducing prejudice makes it potentially applicable to other areas in the world, especially those that are characterized by ethnic tension and violent conflicts.